Pengaruh Kompetensi Kepribadian Guru Pendidikan Agama Kristen Dan Budi Pekerti Terhadap Moralitas Siswa Kelas Ix Smp Negeri 4 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Sarah Br Barus; Simion Harianja; Limmarten Simatupang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to find out whether there is a positive and significant influence between the Personality Competencies of Christian Religious Education Teachers and Character on the Morality of Class IX Students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 Academic Year. The method used in this research uses quantitative methods with descriptive and inferential approaches. The population is all class IX students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year who are Protestant Christians totaling 108 people and a sample of 54 people was determined, namely 50% of the total population using random sampling techniques. Data was collected using a positive closed item questionnaire with 35 items. The results of data analysis show that there is a positive and significant influence of the Christian Religious Education Teacher's Personality Competency and Characteristics on the Morality of Class IX Students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test The value obtained is rxy = 0.586 > rtable(a=0.05,n=54) = 0.226, thus it is known that there is a positive relationship between variable =0.05,dk=n-2=52)= 2,000, thus there is a significant relationship between variable X and variable Y. c) Regression coefficient of determination test (r2) = 34.3%. 2) Influence test: Regression equation test, obtained regression equation Y ̂=26.54+0.67X. Thus Ha is accepted and H0 is rejected.